Nature-Based Solutions for Achieving India’s Net Zero Emission Targets and for Biodiversity Conservation: An Outlook on Agroforestry - Mohankumar, B. (Indian Journal of Agroforestry, 2023)
Climate change and biodiversity loss are two major threats facing humanity today. Nature-based solutions (NbS) are increasingly being considered for neutralizing these negative consequences. India has committed to achieving net zero emission targets by 2070 to offset greenhouse gas emissions – the main driver of climate change. Agroforestry has drawn a lot of attention as a land-management approach with significant promise for combating anthropogenic climate change ever since the latter became a significant worldwide concern in the late 20th century. The underlying notion is that photosynthetic carbon fixation by trees is an efficient strategy for reducing the increase of carbon dioxide concentrations in the atmosphere and agroforestry systems (AFS) endow better rates of carbon sequestration than treeless arable crop systems. Agrobiodiversity, a subset of biodiversity that encompasses all crops and livestock in addition to all interacting species of pollinators, symbionts, pests, parasites, predators, and rivals, is also under threat owing to agricultural intensification and other related processes. Most tropical AFS, especially the multistrata systems, are inherently capable of fostering aboveground and belowground biodiversity and represent remarkable loci for agrobiodiversity conservation (circa situm reservoirs of biodiversity). The high carbon sequestration potential AFS also implies that it can contribute significantly to the country’s aspirations of reaching net-zero emissions by 2070.